Role of SNARE Proteins in the Insertion of KCa3.1 in the Plasma Membrane of a Polarized Epithelium - Farquhar, Rachel E.; Cheung, Tanya T.; Logue, Matthew J. E.; McDonald, Fiona J.; Devor, Daniel C.; Hamilton, Kirk L. (Frontiers in Physiology, 2022)
Targeting proteins to a specific membrane is crucial for proper epithelial cell function. KCa3.1, a calcium-activated, intermediate-conductance potassium channel, is targeted to the basolateral membrane (BLM) in epithelial cells. Surprisingly, the mechanism of KCa3.1 membrane targeting is poorly understood. We previously reported that targeting of KCa3.1 to the BLM of epithelial cells is Myosin-Vc-, Rab1-and Rab8-dependent. Here, we examine the role of the SNARE proteins VAMP3, SNAP-23 and syntaxin 4 (STX-4) in the targeting of KCa3.1 to the BLM of Fischer rat thyroid (FRT) epithelial cells. We carried out immunoblot, siRNA and Ussing chamber experiments on FRT cells, stably expressing KCa3.1-BLAP/Bir-A-KDEL, grown as high-resistance monolayers. siRNA-mediated knockdown of VAMP3 reduced BLM expression of KCa3.1 by 57 ± 5% (p ≤ 0.05, n = 5). Measurements of BLM-localized KCa3.1 currents, in Ussing chambers, demonstrated knockdown of VAMP3 reduced KCa3.1 current by 70 ± 4% (p ≤ 0.05, n = 5). Similarly, siRNA knockdown of SNAP-23 reduced the expression of KCa3.1 at the BLM by 56 ± 7% (p ≤ 0.01, n = 6) and reduced KCa3.1 current by 80 ± 11% (p ≤ 0.05, n = 6). Also, knockdown of STX-4 lowered the BLM expression of KCa3.1 by 54 ± 6% (p ≤ 0.05, n = 5) and reduced KCa3.1 current by 78 ± 11% (p ≤ 0.05, n = 5). Finally, co-immunoprecipitation experiments demonstrated associations between KCa3.1, VAMP3, SNAP-23 and STX-4. These data indicate that VAMP3, SNAP-23 and STX-4 are critical for the targeting KCa3.1 to BLM of polarized epithelial cells.